2020
DOI: 10.1097/md.0000000000020640
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of local infiltration analgesia for pain management in total knee and hip arthroplasty

Abstract: Background: Local infiltration analgesia (LIA) has become popular in postoperative pain relief after total hip arthroplasty (THA) or total knee arthroplasty (TKA). The aim of this meta-analysis was to compare the efficacy and safety of LIA with intrathecal morphine and epidural analgesia after THA and TKA. Methods: A systematic article search was performed from PubMed, Embase, and Web of Science databases, up to February 21, 2019. The main outcomes incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…In order to confirm Kerr and Kohan's findings, several studies have been executed. Conflicting evidence has been reported [2][3][4][5][6]8,9,11,12,[14][15][16][17][18][19] . However, consulting and summarizing the literature to date, The Enhanced Recovery consumption of piritramide or tramadol, but an analysis of binary results whether the patients had taken opioids at all.…”
Section: Discussionmentioning
confidence: 99%
“…In order to confirm Kerr and Kohan's findings, several studies have been executed. Conflicting evidence has been reported [2][3][4][5][6]8,9,11,12,[14][15][16][17][18][19] . However, consulting and summarizing the literature to date, The Enhanced Recovery consumption of piritramide or tramadol, but an analysis of binary results whether the patients had taken opioids at all.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Also in line with previous studies, we showed a mutually indistinguishable effect of LIA and FSNB 24 hours after surgery, 38 which was superior to the effects of post-op epidural opioids and intrathecal analgesics. 39 , 40 Since the systemic toxicity of LIA can affect up to 11% of patients, the post-op monitoring of LIA patients cannot be ignored. 41 A similar observation was made by Tian et al; their retrospective TKA study showed that the short-term analgesic effect of LIA was similar to that of nerve block and reduced the need for opiate supplementation, and that LIA and nerve block had similar complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Es werden lokal und oral wirksame Analgetika eingesetzt – unter Berücksichtigung der Nebenwirkungsprofile eingesetzter Pharmazeutika, insbesondere auch der Opioide, die zurückhaltend eingesetzt werden sollten. Der Einsatz einer lokalen Infiltrationsanalgesie (LIA) in Kombination mit oralen Analgetika wird in der Knieendoprothetik favorisiert und ist auch an der Hüfte weit verbreitet [ 3 , 14 , 16 , 34 , 38 , 41 , 47 ]. Es wurden eine Reduktion des postoperativen Schmerzes, eine Verbesserung der Funktion sowie eine Reduktion der Dauer des Krankenhausaufenthaltes beschrieben [ 4 , 14 , 36 , 44 ].…”
Section: Grundlagenunclassified
“…Im Rahmen von Fast-Track-Konzepten wird in aller Regel gänzlich auf die Einlage von Wunddrainagen verzichtet, da diese die Beweglichkeit und selbstständige Mobilisation der Patienten beeinträchtigen sowie Schmerzen verursachen können, ohne einen Effekt auf das Auftreten postoperativer Wundinfektionen, die Häufigkeit von Wundverbandwechseln, Schwellung, postoperative Schmerzen oder die Rate thrombembolischer Ereignisse zu haben [ 50 ]. Zudem lässt sich durch den Verzicht eine Senkung der Transfusionsrate erzielen [ 37 , 38 ]. Ergänzend können moderne transparente und wasserdichte Pflasterverbände verwendet werden, die die sonst häufiger notwendigen Verbandswechsel überflüssig machen und das Risiko einer Wundkontamination mindern.…”
Section: Grundlagenunclassified